Romance revisited: quiltmaking in the twenty-first century - Hodapp, Angela, author; Sloane, Sarah, advisor; Cowell, Pattie, committee member; Griffin, Cindy, committee member (Colorado State University. Libraries, 2010)
The first twentieth-century American quilt revival lasted from the century's earliest years through the Depression; the second-the current revival-began around the time of America's bicentennial in 1976. In 1915, author Marie D. Webster identified three hallmarks of the revival of her time. She claimed that the increasing demand for competent quilters, the desire for new quilt patterns, and the growing popularity of quilt exhibitions were evidence of that revival. In this collection of creative nonfiction essays, which are largely based on my personal experiences as a quiltmaker and as the editor of a leading quilt magazine, I compare the revival of Webster's time with the revival of mine. Taking each of Webster's hallmarks in turn, I discuss quilting for hire; the mechanization of quiltmaking; the commercialization of the quilt industry; intellectual property rights as they apply to quilts; the ethics of entering, producing, and judging quilt contests; and predictions for the future of quiltmaking in America.
Keywords: Quilting